Aspectos clássicos de teorias de segunda ordem - Pompéia, P. J [UNESP] (2009)
In this work, classical and semiclassical aspects of second order theories were analyzed. First the formulation of a gauge theory for systems whose Lagrangian for the gauge field depends on the field itself and its first and second derivatives was proposed. Applications of this structuire for the U(1) group - Podolsky generalized electodynamics - and for SU(N) - Alekseev, Abuzov e Baikov effective Lagrangian - were made. The Lorentz group SO(3,1) was also analyzed and an isotropic and static solution in linear approximation was obtained for a particular case. Next it was analyzed how Podolsky thory could be constrainedin three different ways using experimetnal data available on the literature. Finally the non-relativistic limits of Podolsky electrodyamics were analyzed on the 5-dimensional galilean formalism. The electric and magnetic limits were obtained